The Effect of Active Learning Index Card Match Strategy to Ward Communication Ability of Mathematic of For Students of MTs AL-Fajar Pekanbaru - Guswinda, Guswinda (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The objective of study was to find whether there is or not the effect of mathematic communication ability for students learned using active learning index card match strategy and the study learned using conventional strategy. The formulation of study was whether there is or not the effect of active learning index card match strategy toward communication ability of mathematic of for students of MTs AL-Fajar Pekanbaru?.Where research is a Quasi Experiment. The population in this study were students of class VIII MTs Al-Fajar Pekanbaru a total of 98 students were divided into 3 class. The sampel of this research is to the experimental group with active learning index card match strategy VIII B class by 33 students and the control group with convensional learning VIII A class by 32 students. Thus the number of the whole sample was 65 students. The data was collected using observation, test and documentation. In this study, meeting were held six times in the four meeting by using the Active Learning Index Card Match Strategy and the two meeting held pretest and posttest. Data analysis techniques used in this research is a test-t for a large sample (N â¥ 30). From the data analyisis performed by the Active Learning Index Card Match Strategy obtained tithing value = 3,06 which means greater than tt> both at significance level 5% and 1% namely 2,65 < 3,06 > 2,00 so that the zero hypothesis is rejected and the alternative hypothesis is accepted. Because of the presence of these difference, it can be said there are significant active learning index card match strategy toward communication ability of mathematic of for students of MTs Al Fajar Pekanbaru.